Diversification and prevalence of the quinolone resistance crpP genes and the crpP-carrying Tn6786-related integrative and conjugative elements in Pseudomonas aeruginosa. Issue 1 (1st January 2021) - Zhu, Zhichen; Yang, Huiying; Yin, Zhe; Jing, Ying; Zhao, Yuee; Fu, Hongyu; Du, Hong; Zhou, Dongsheng
ABSTRACT: The quinolone resistance crpP genes can mediate decreased susceptibility to quinolones. However, diversification and prevalence of crpP genes and crpP -carrying integrative and conjugative elements (ICEs) still need to be elucidated. In this study, genome sequencing was conducted for 200 Chinese Pseudomonas aeruginosa isolates, 16 of which were fully sequenced. All the 37 available CrpP variants were collected for phylogenetic analysis, 10 CrpP enzymes were chosen to conduct cloning and antimicrobial susceptibility test, and 22 crpP -carrying Tn 6786 -related ICEs were selected for detail genetic dissection analysis. Then, typing/nomenclature schemes for crpP variants and crpP -carrying ICEs were established for the first time. The 10 representative CrpP enzymes were confirmed to mediate decreased susceptibility to one to three quinolones. Tn 6786 -related ICEs displayed high-level diversification in both nucleotide sequences and modular structures. Mainly, massive gene acquisition/loss occurred across the whole genomes of Tn 6786 -related ICEs. 53.5% (107/200) of the tested clinical P. aeruginosa isolates from China carried crpP genes, which were exclusively located within chromosome-borne Tn 6786 -related ICEs. The crpP -carrying ICEs were at active stages of evolution and had the high potential to be an important vector for the dissemination of resistance genes besides crpP . The present study furthered the understanding of the bioinformatics and epidemiology of crpP genes and crpP -carrying ICEs.